2019
DOI: 10.3389/fmicb.2019.01107
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Whole-Genome Sequencing Data Into Quantitative Risk Assessment of Foodborne Antimicrobial Resistance: A Review of Opportunities and Challenges

Abstract: Whole-genome sequencing (WGS) will soon replace traditional phenotypic methods for routine testing of foodborne antimicrobial resistance (AMR). WGS is expected to improve AMR surveillance by providing a greater understanding of the transmission of resistant bacteria and AMR genes throughout the food chain, and therefore support risk assessment activities. At this stage, it is unclear how WGS data can be integrated into quantitative microbial risk assessment (QMRA) models and whether their integration will impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 132 publications
0
83
0
Order By: Relevance
“…Another study suggested that pathogenicity may be linked to genome reduction rather than the acquisition of certain VGs 40 . It is therefore likely that traditional pathotyping schemes will be modified in the future and that multi-omic pathogenicity predictive models that consider the presence and expression of all genes rather than small sets will gain more ground as genome databases grow 11 . Nevertheless, the virulence gene repertoire of ESBL/pAmpC-EC reported here and in other studies, may explain their adaptation to and persistence in various niches, such as the poultry environment 41 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study suggested that pathogenicity may be linked to genome reduction rather than the acquisition of certain VGs 40 . It is therefore likely that traditional pathotyping schemes will be modified in the future and that multi-omic pathogenicity predictive models that consider the presence and expression of all genes rather than small sets will gain more ground as genome databases grow 11 . Nevertheless, the virulence gene repertoire of ESBL/pAmpC-EC reported here and in other studies, may explain their adaptation to and persistence in various niches, such as the poultry environment 41 .…”
Section: Resultsmentioning
confidence: 99%
“…However, our study has limitations. Quantitative estimates on transmission pathways as well as statistical associations between the identified genotypes, which are essential for QMRAs, cannot be inferred with our analysis since this would require the www.nature.com/scientificreports/ sequencing of a larger and more representative part of our initial collection of isolates 11 . Such approaches are hampered by the decreasing but still significant cost of WGS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antimicrobial resistance (AMR) has become great concern worldwide in the clinical field as well as in the field of food production and distribution, or the food chain (1)(2)(3)(4)(5)(6)(7). Carbapenem resistance is one of the most severe forms of AMR (1,8), and carbapenemase [a subgroup of β-lactamase (bla)]-producing bacteria, such as carbapenemase-producing Enterobacteriaceae, are spreading worldwide (9,10).…”
Section: Introductionmentioning
confidence: 99%